Comparison of lignin and IVDMD technique for estimation of dry matter intake and digestibility in range managed sheep - Shinde, A K; Sankhyan, S K; Bhatta, R; Karim, S A (The Indian Journal of Animal Sciences, 2012)
The study was conducted to compare lignin ratio (LR) and in vitro DM digestibility (IVDMD) techniques as methods for estimating in vivo DMI and digestibility of pasture vegetation in range managed sheep. Four intact and 2 oesophageal cannulated rams were allowed to graze on cenchrus pasture throughout the year. The digestion trials were conducted in monsoon, winter and summer. In each trial total faeces from 4 intact ram was collected for 5 days by titting harness and faecal bags. During the same period diet samples. were collected from 2 oesophageal cannulated rams. Lignin content of oesophageal extrusa increased from monsoon to winter and summer with similar seasonal trends in its voidance in the faeces. The faecal output also varied in the seasons commensurating with DMI of the animals. Correlation coefficient of faecal output with DMI of animals pooled for 3 seasons and 2 methods were 0.89, DMI was over estimated by 4.8 % in monsoon and 7.3 % in summer using IVDMD compared to LR method, while DMD estimated by both the methods was similar in winter. Similar seasonal trends were observed in estimation of DMI by the 2 methods from total faecal DM voided. The DMI could be predicted with 91-93% confidence by the 2 faecal sampling methods. Thus it is concluded that rVDMD and LR methods estimate similar DMI and DMD in grazing sheep.